Scenario of power distribution network in the City of Dhaka in the context of reliability - Hoque, Mohammed Tariqul; Karim, A.N. Mustafizul; Haque, A. F. M. Anwarul (The Institution of Engineers (IEB), Bangladesh, 2003)
In the modern world, the importance of uninterrupted supply of electricity cannot be overemphasized. Per capita consumption of electricity is universally adopted as a yardstick of the living standard of a nation. Three principal components in a typical electrical power supply system are (a) the generating plant (b) the transmission system and (c) the distribution network. All of these components must function properly to ensure the quality of electricity supplied.